Genetic diversity of Mangifera indica (Anacardiaceae) in Valencia, Córdoba, Colombia, using microsatellite markers - Guerra, Martha; Ruiz, Rosalba; Pardo Pérez, Enrique (Instituto de Ecología, A.C., 2018)
Background and Aims: Mango (Mangifera indica) belongs to the Anacardiaceae family and is native to South Asia. It has currently reached a large distribution because of its development in warm climates, and its adaptation to a wide range of environmental conditions. Knowledge of the population genetic diversity of mango germplasm in Valencia, Córdoba, Colombia, would allow for selection of promising mango varieties and populations for use in the country's breeding programs. The aim of the present work was to determine the genetic diversity of a population of Mangifera indica in Valencia using 12 microsatellite markers.Methods: The study was conducted with leaves of Mangifera indica collected in the city of Valencia and dehydrated with silica gel. The analysis of individuals was performed using 12 microsatellite molecular markers. Employing different software (GENALEX, CERVUS, FSTAT and MEGA 7), were determined: number of alleles, effective number of alleles, heterozygosity observed and expected, genetic distance, Hardy-Weinberg equilibrium, polymorphic information content, fixation indices FIS, FIT, FST and a dendrogram.Key results: All microsatellites used were polymorphic. Between 5 to 12 alleles were detected, with an average of 7 alleles per locus and a total of 84. The average effective number of alleles was 4.551. PIC values ranged between 0.86 and 0.49 for MiIIHR23 and MiIIHR34 respectively. The Hardy-Weinberg test indicated that the population was in disequilibrium (p<0.05) for the 12 markers. The fixation index revealed an excess of homozygotes. The average of the observed and expected heterozygosity was 0.355 and 0.748 respectively.Conclusions: The analyzed population presented high genetic diversity and the markers were very informative, attending the PIC.